Treating personality disorder: creating robust services for people with complex mental health needs - Murphy, Naomi (Routledge, 2010)
The difficulties that staff experience in treating individuals with personality disorder / Naomi Murphy & Des McVey -- Assessing personality disorder within a formulation framework / Jacquie Evans and Neil Watson -- Delivering integrated treatment to people with personality disorder / Jacqui Saradjian, Naomi Murphy, and Des McVey -- Fundamental treatment strategies for optimising interventions with people with personality disorder / Naomi Murphy & Des McVey -- Organisational challenges to providing services for personality disordered people / Des McVey and Jacqui Saradjian -- Effective transdisciplinary teamworking / Naomi Murphy -- The role of the nurse in treating people with personality disorder / Des McVey -- The role of the occupational therapist in treating people with personality disorder / Leanne Jones -- The role of the prison officer : (dangerous and severe personality disorder in the prison system) / Stephen Fox -- The role of the psychiatrist in treating personality disorder / Valerie Hawes -- Beyond therapy : the wider role of the psychologist in treating personality disorder / Jo Ramsden -- Issues and challenges for the clinical professional / Elizabeth Sneath